Human exploitation and conservation of sea snakes In Sabah - Anna Wong (Penerbit UMS, 2006)
This study looks into the exploitation of sea snakes in relation to fish harvesting where sea snakes are frequently caught in fishing nets, on the west coast of Sabah. Commercial fishing operations have increased tremendously, with a 36-fold increase of marine fish landing by using trawl nets since 1988 to 1997. This study found that mean number of sea snakes caught per trawl was 23 specimens, and 46 sea snakes per trawler per landing. For the last ten years, a total of I .3 million sea snakes are estimated to have died. It is remarkable that trawler killed more than six hundred thousand sea snakes per year recently, yet the sea snakes continued to survive. Compared with the previous study (carried out 10 years ago before this study), the species diversity and abundance of sea snakes on the west coast of Sabah is still high. This might be explained by the presence of suitable habitats. adequate food resources and healthy environment.